International Aid and Sustainable Development in North Korea: A Country Left Behind with Cloaked Society - Sojin Lim (Routledge, 2024)
This book examines international aid in North Korea, in particular the ongoing policy of withholding aid, through the lens of the impact on the general population to present an argument for sustainable development. Focusing on the human rights of North Koreans and presenting a case for the use of aid as a provision for social change, it explores an alternative narrative to the existing long-drawn-out rhetoric of 'denuclearisation-first'. The book's scope includes evaluations of the causes of international sanctions and their impact, the Kim regime's mitigation of sanctions through marketisation and a digital economy as well as barriers to aid monitoring and the reason for the absence of any mass anti-regime movement. It also posits that North Korea is a fragile state but cloaked by the image of a strong regime. The book succinctly demonstrates that the key to unlocking the potential of North Korea's 'cloaked society' does not lie in sanctions, but is to be found in engagement with development aid. As such it will appeal to students of Korean Studies, Development Studies, Asian Politics and International Relations. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.
Keywords: 330; Marketisation; Digital Economy; Nuclear Programme; UN; Sanctions; Famine; North Korean; Civil Society; North Korean Society; North Korean Regime; Humanitarian Aid; Ordinary North Koreans; UNSC Resolution; Cee Country; Street Level Bureaucrats; International Aid; Kim Regime; North Korea's Nuclear Programme; KEDO; FSI; Fragility Index; State Capacity Development; Fragile States; ICBM Launch; Fourth Nuclear Test; USD Million; North Korean Defectors; Armoured Combat Vehicles; Ballistic Missile Programmes; Loan Aid